2001
DOI: 10.1246/cl.2001.622
|View full text |Cite
|
Sign up to set email alerts
|

MMA Modified Inorganic/Organic Hybrid Membranes by Sol–Gel Technology

Abstract: The inorganic/organic hybrid membranes modified by MMA were deposited on the porous α-Al2O3 substrates (pore size, 2 µm) by the sol–gel technology. It was found that the introduction of MMA can not only improve the membrane formation properties, but also increase the selectivity of O2/N2 and O2/CO2. On the other hand, the modified hybrid membranes have more dense structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…This is consistent with gas separation results [6]. The introduction of MMA to the hybrid membrane improved the separation factor of O 2 /N 2 and O 2 /CO 2 , but reduced the permeation rate [7]. The gas permeation calculation also proved this point.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…This is consistent with gas separation results [6]. The introduction of MMA to the hybrid membrane improved the separation factor of O 2 /N 2 and O 2 /CO 2 , but reduced the permeation rate [7]. The gas permeation calculation also proved this point.…”
Section: Resultssupporting
confidence: 87%
“…The error between the tested data and calculation value is small and the results are relatively credible. Gas separation performance showed that the hybrid membrane have good separation factor at relatively low pressure below 0.2 MPa, the gas transport in the membrane is mainly due to the surface diffusion and Knudsen diffusion [6][7]. When the pressure is above 0.2 MPa, the separation factor decreased with the pressure drop increase, the gas transport in the membrane is contributed to the Knudsen and Poiseuille diffusion.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations